20α- and 20β-dihydrocortisone may interfere in LC-MS/MS determination of cortisol in saliva and urine. (May 2018) - Israelsson, Marlen; Brattsand, Ralph; Brattsand, Göran
Background: LC-MS/MS methods offer high selectivity in cortisol determinations. However, endogenous steroid metabolites may still interfere and compromise the results, for example in the diagnosis of Cushing's syndrome. Erroneously elevated cortisol may, in particular, be misleading at the low concentrations found in salivary samples obtained at late night and after dexamethasone suppression. Methods: Interferences in our LC-MS/MS method used for determination of cortisol in saliva and urine were identified by comparing their retention times and mass spectra with those of pure candidate substances. The chromatographic conditions used in our LC-MS/MS method, including column and mobile phase gradient, were varied in order to separate the target compound from the interferences. Results: Two interferences, which were co-eluting or eluting close to cortisol in our original method, were successfully separated from cortisol by adjustment of the chromatographic conditions. These interferences were found in both urine and saliva and were identified as the two endogenous cortisol isomers 20α- and 20β-dihydrocortisone. The isomers share molecular mass and mass spectrometric fragmentation pattern with cortisol using electrospray ionization in the positive-ion mode. Both give rise to the transitions m/z 363.1>121.1, 363.1>115.1 and 363.1>97.1. In our original LC-MS/MS setup, the 20β-dihydrocortisone co-eluted with cortisol in the chromatography step resulting in false high determinations. Conclusions: Cortisol determination by LC-MS/MS may suffer from erroneously elevated results unless 20α- and 20β-dihydrocortisone are chromatographically separated from cortisol.